Assessment of Studying Books as the Original Source of Knowledge Acquisition by the Top-Level Managers in Zinc Industry - Jafari, Mostafa; razzaghi, Eshagh (Advances in Social Sciences Research Journal, 2017)
Which are the main acquisition resources of formal and informal knowledge for Top-level industrial managers? How are these resources utilized and when are they get used? How are the quality and quantity of these knowledge acquisition resources assessed? This research tries to explore these three questions.